Object lessons: the question of cultural property in the age of repatriation - Michael E. Harkin (Journal de la Société des Américanistes)
Object lessons: the question of cultural property in the age of repatriation. Northwest Coast material culture has become increasingly identified as cultural property, a quasi-legal concept that denotes objects of a collective patrimony. This represents a radical shift from earlier notions of property, seen strongly as privately owned by individuals and family groups. Moreover, the status of these objects as art, that is, framed in a museum setting and partaking of certain transcendent qualities derived from the Western tradition, represents a dramatic redefinition of pieces that were considered analogous to human beings, as temporary entities. This process of redefinition, which is generational, political, and an invention of tradition, is probably inevitable.